2016
DOI: 10.1155/2016/2470351
|View full text |Cite
|
Sign up to set email alerts
|

The Signaling Pathways Involved in Chondrocyte Differentiation and Hypertrophic Differentiation

Abstract: Chondrocytes communicate with each other mainly via diffusible signals rather than direct cell-to-cell contact. The chondrogenic differentiation of mesenchymal stem cells (MSCs) is well regulated by the interactions of varieties of growth factors, cytokines, and signaling molecules. A number of critical signaling molecules have been identified to regulate the differentiation of chondrocyte from mesenchymal progenitor cells to their terminal maturation of hypertrophic chondrocytes, including bone morphogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 140 publications
(147 reference statements)
0
92
0
1
Order By: Relevance
“…The progression of in vivo endochondral ossification is thought to be controlled by a number of cytokines, with BMPs, IHH/PTHrP, and Wnt/beta-catenin, providing key pathways to regulate bone formation. [49][50][51] In previous studies, cytokines produced by differentiated hypertrophic chondrocytes influenced bone formation and remodeling. 52 In this study, the flow rate did not affect the BMP concentration, indicating that the BMP pathways activated by the tissue-engineered grafts upon implantation did not play a significant role in bone regeneration.…”
Section: Discussionmentioning
confidence: 95%
“…The progression of in vivo endochondral ossification is thought to be controlled by a number of cytokines, with BMPs, IHH/PTHrP, and Wnt/beta-catenin, providing key pathways to regulate bone formation. [49][50][51] In previous studies, cytokines produced by differentiated hypertrophic chondrocytes influenced bone formation and remodeling. 52 In this study, the flow rate did not affect the BMP concentration, indicating that the BMP pathways activated by the tissue-engineered grafts upon implantation did not play a significant role in bone regeneration.…”
Section: Discussionmentioning
confidence: 95%
“…The study of all these phenomena constitutes the field of cellular stress biology, which has been separated from “normal” developmental biology and physiology for decades. Increasingly, however, the boundary between these fields is blurred because mechanisms and agents common to the field of stress biology, such as apoptosis or ROS, have been found to play a role in “normal” biological processes like cell differentiation . This overlap between stress biology and developmental biology is not coincidental.…”
Section: Cellular Stress Is Counteracted By Conserved Molecular Mechamentioning
confidence: 99%
“…SOX9 binds to the promoter region of the collagen type II gene and results in the expression of the said gene. It is reported that in the absence of SOX9, the chondrogenesis is blocked at the initial stages of mesenchymal condensation and hence forms a critical marker . The nondifferentiated state of stem cells, as well as fibrocartilage initiation, is evaluated by the expression of collagen type 1 gene .…”
Section: Discussionmentioning
confidence: 99%